Kohesi Sosial dan Ancaman Media Sosial terhadap Keluarga di Era Digital - Maihasni Maihasni; Fachrina Fachrina; Nini Anggraini; Ariesta Ariesta (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study examines social cohesion within the family and the potential threats posed by social media use in the digital era. It focuses on identifying specific forms of disruption to family cohesion and the adaptive strategies families employ in response. The research was conducted in Padang City using a qualitative approach with a descriptive design. Data were collected through in-depth interviews and participatory observation, with families as the unit of analysis. The data analysis followed a three-stage interactive model comprising data reduction, data display, and conclusion drawing. The findings reveal that social media negatively affects familial relationships, as reflected in altered communication patterns, reduced empathy and concern, stronger privacy boundaries, and the emergence of mutual suspicion. In response, families adopt strategies such as mindful management of social media use, heightened awareness of digital risks, and the reinforcement of interpersonal communication to preserve social cohesion within the household.